'[C]allee me Oscar': The Picture of Dorian Gray, Aestheticism, and Opium. (March 2019) - Wu, Ya-feng
Abstract : Oscar Wilde's only novel, The Picture of Dorian Gray (1891), one of the flagship novels of Aestheticism, contains an intricate opium narrative that has yet to receive adequate critical attention. The novel consists of two nested units: the House Beautiful that subsumes a Gothic nursery where Dorian's portrait is placed, and London the Metropolis that harbours Blue Gate Fields in the East End. The former might be read as a miniature of the latter. This double mechanism hinges on a Chinese box in which opium is stored. The structure, which evolves from the classic opium narrative established by Thomas De Quincey's Confessions of an English Opium Eater (1821), enables Wilde to stage a critique on the connection between Aestheticism and the imperial trade of opium. Besides, Wilde's aesthete trio in the novel, Lord Henry Wotton, Dorian Gray, and Adrian Singleton, are cast as opium smokers in order to disrupt the imperialist mindset showcased in the cartoons appearing on trade cards and in magazines that satirise Wilde's promotion of Aestheticism. This essay contends that Wilde's opium narrative exposes the hypocrisy of Empire by demonstrating that the coloniser and the colonised are anamorphic reflections of each other.